Problematika Pendidikan Agama Islam di Sekolah Umum - Rizki Safitri Yanwari; Deddy Ramdhani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study is to gain a better understanding of the problems of Islamic Religious Education taught in non-Islamic educational institutions. Learning Islamic Religious Education in schools is a basic learning that students must learn. However, many students are bored and take part in PAI learning in the classroom. Even though the hope is that Islamic Religious Education is able to encourage students to behave and have good ethics. The method used in this study is a qualitative approach that adopts a descriptive model from literature studies. The analysis process uses content analysis methods, with the main focus on various journals that discuss challenges in Islamic religious education in various schools in Indonesia. The results of this study indicate that PAI problems in schools are caused by two factors, namely internal and external factors. Internal factors are caused by school management, education, facilities and infrastructure, and based on the curriculum. While the external factors are caused by the low interest in learning students and the mini-motivation to learn.